Empirical finding on the determinants of collective consumption: Focused on consumption values, trust, and perceived risk - Yoon Joo Park; Sungjoon Yoon (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The rapid advances in information and communications technologies, combined with increased social awareness of today's consumers, ushered in transformation in consumers' purchase behavior. This big shift away from the traditional ownership-based economy into a sharing economy is causing an urgent necessity to understand the shifted decision mechanism. Although there have been quite a few previous studies on antecedents of consumers' decision to engage in collective consumption, it is somewhat difficult to find previous research that focused on consumption values as antecedent predictors. To abridge this gap, this study aims to determine whether two predictors (social value and ethical value) affect consumers' intention to utilize collective consumption. In addition, the current study verifies the role of perceived risk as a moderator between perceived trust and the intention to use collective consumption. For the purpose of hypothesis verification, the study uses multiple regression and hierarchical moderated regression analysis. Responses from a total of 246 respondents are used for statistical analysis. The respondents were selected from the students attending a university located in Seoul, South Korea. The results indicate that social value and ethical value exerted significant impacts on the perceived trust of collective consumption. However, the magnitude of the social value's impact was slightly greater than that of ethical value. The result also confirms the mediating role of the perceived trust. Furthermore, perceived risk moderated the relationship between trust and the intention to utilize collective consumption.
Keywords: 650; collective consumption; ethical value; perceived risk; social value; trust